2013
DOI: 10.21432/t22010
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Using Tablet Technology in Post-Secondary Classes / Perceptions des étudiants quant à l’utilisation des tablettes électroniques dans les classes universitaires

Abstract: This paper assesses students’ attitudes towards using tablets, such as the Apple iPad, in university classes. Tablets are found to be a substitute for laptop computers. Students initially expressed a great deal of optimism regarding the technology, and, although their views diminished slightly as they gained experience with using a tablet, their attitude towards the technology remained overwhelmingly positive. Most students experienced an easy transition from using a laptop to using a tablet. Furthermore, once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
1
1
1
Order By: Relevance
“…While the survey results showed that students used tablets for the purpose of learning such as taking notes during lectures, interview results revealed that students were involved more with social media than the lecture. On the other hand, responses received from 80% of the students were that they did not use it for non-learning activities during class hours which is inconsistent with the findings by Mang and Wardley (2013) who indicate that checking personnel emails and social networking in class declined students from focusing on the lecture. The researchers of the current study observed that these off-task behaviours could be due to some students who do not know the positive side of using tablets for learning.…”
Section: Discussioncontrasting
confidence: 65%
“…While the survey results showed that students used tablets for the purpose of learning such as taking notes during lectures, interview results revealed that students were involved more with social media than the lecture. On the other hand, responses received from 80% of the students were that they did not use it for non-learning activities during class hours which is inconsistent with the findings by Mang and Wardley (2013) who indicate that checking personnel emails and social networking in class declined students from focusing on the lecture. The researchers of the current study observed that these off-task behaviours could be due to some students who do not know the positive side of using tablets for learning.…”
Section: Discussioncontrasting
confidence: 65%
“…Τα τελευταία έτη παρατηρείται στην εκπαιδευτική κοινότητα μία παγκόσμια προσπάθεια ενσωμάτωσης σύγχρονων εφαρμογών στην εκπαιδευτική πρακτική με βασικό στόχο την ανταπόκριση του σχολείου στις τρέχουσες εξελίξεις (Φωκίδης & Φωνιαδάκη, 2017). Πιο συγκεκριμένα, οι εφαρμογές της επαυξημένης πραγματικότητας (Augmented Reality -AR) επιχειρούν να συνδέσουν την υπαρκτή με την εν δυνάμει υπαρκτή πραγματικότητα και δύναται να συνδράμουν, σύμφωνα με διεθνείς έρευνες, στη μαθησιακή διαδικασία προσφέροντας καινοτόμες ιδέες για την επίτευξη των εκάστοτε παιδαγωγικών στόχων (Bidin Mang & Wardley, 2013). Η μάθηση με τη χρήση των Νέων Τεχνολογιών (ΝΤ), προσφέρει έναν πρωτότυπο τρόπο προσέγγισης της εκπαιδευτικής πρακτικής, κρατώντας σε εγρήγορση τους/τις μαθητές/τριες καθ' όλη τη διάρκεια της διδακτικής ώρας (Μουστάκας κ.ά., 2015).…”
Section: εισαγωγήunclassified
“…Second, the size of the screen may make it difficult to simultaneously view a source document and write another document [6]. Further, the virtual keyboard of the tablet may reduce screen visibility [7]. Finally, traditional document study applications (e.g.…”
Section: Introductionmentioning
confidence: 99%